The Effect of Humic Acid on Shallots Growth and Yield In Brebes - Sri Wahyuni; Hana Fadila; Muhammad Abdul Aziz; Valdi Muhammad Rafiansyah Siregar; Fauziatul Fitriyah; Soekarno Mismana Putra; Poppy Arisanty; Sulastri Sulastri; Insyiah Meida Luktyansyah; Priyono Priyono; Siswanto Siswanto (Institut Pertanian Bogor, 2026)
The effectiveness of humic acid application in increasing shallot yields for farmers must be studied, particularly in terms of quality and quantity. It is also consistent with the relatively high consumption and public demand for shallots year after year. The purpose of this study was to examine how humic acid spraying affects shallot growth and production. Humic acid was applied in two stages: fertilizer coating and foliar spray, with varying treatment dosages. Field testing was conducted in two trials. The initial test revealed that the treatment plants grew faster than the control plants, potentially increasing yields by 7−15%. The validation test (second test) with three treatments yielded the same results: treatment plants outgrew the control specimen, increasing yields by 20−25%. Based on these findings, the use of humic acid may be an alternative for enhancing the agricultural industry, particularly in shallots. Keywords: coating, fertilization effectiveness, foliar spray